Novel Toxicology Program to Support the Development of Inhaled VentaProst. (September 2020) - Tepper, Jeffrey; Pfeiffer, Juergen; Bujold, Kim; Fink, James B.; Malcolmson, Richard; Sullivan, Dennis; Authier, Simon; Entcheva-Dimitrov, Plamena; Clark, Andrew
Currently, off-label continuous administration of inhaled epoprostenol is used to manage hemodynamics during mitral valve surgery. A toxicology program was developed to support the use of inhaled epoprostenol during mechanical ventilation as well as pre- and postsurgery via nasal prongs. To support use in patients using nasal prongs, a Good Laboratory Practice (GLP), 14-day rat, nose-only inhalation study was performed. No adverse findings were observed at ∼50× the dose rate received by patient during off-label use. To simulate up to 48 hours continuous aerosol exposure during mechanical ventilation, a GLP toxicology study was performed using anesthetized, intubated, mechanically ventilated dogs. Dogs inhaled epoprostenol at approximately 6× and 13× the dose rate reported in off-label human studies. This novel animal model required establishment of a dog intensive care unit providing sedation, multisystem support, partial parenteral nutrition, and management of the intubated mechanically ventilated dogs for the 48-hour duration of study. Aerosol was generated by a vibrating mesh nebulizer with novel methods required to determine dose and particle size in-vitro. Continuous pH 10.5 epoprostenol was anticipated to be associated with lung injury; however, no adverse findings were observed. As no toxicity at pH 10.5 was observed with a formulation that required refrigeration, a room temperature stable formulation at pH 12 was evaluated in the same ventilated dog model. Again, there were no adverse findings. In conclusion, current toxicology findings support the evaluation of inhaled epoprostenol at pH 12 in surgical patients with pulmonary hypertension for up to 48 hours continuous exposure.